2017
DOI: 10.1590/0370-44672016700094
|View full text |Cite
|
Sign up to set email alerts
|

Wear resistance of AISI 304 stainless steel submitted to low temperature plasma carburizing

Abstract: Despite the AISI 304 stainless steel has high corrosion/oxidation resistance, its tribological properties are poor, being one of the barriers for use in severe wear applications. Thus, there is a wide field for studying technologies that aim to increase the surface hardness and wear resistance of this material. In this work, hardness and wear resistance for AISI 304 stainless steel submitted to the thermochemical treatment by low temperature plasma carburizing (LTPC) in a fixed gas mixture composition of 93% H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 16 publications
0
5
0
Order By: Relevance
“…They reported that SMA treatment is effective in reducing material removal by 2 to 4 times under all combined sliding wear and electrochemical conditions due to surface and sub-surface hardening effect induced by SMA process. Improved tribological properties have been found for low-temperature plasma carburizing (LTPC) treated AISI 304 during pin-on-disc wear test [14]. Previously, 2D parameters such as root mean square roughness (R q ), skewness (R sk ), and kurtosis (R ku ) have been used for characterizing the worn surfaces.…”
Section: Introductionmentioning
confidence: 99%
“…They reported that SMA treatment is effective in reducing material removal by 2 to 4 times under all combined sliding wear and electrochemical conditions due to surface and sub-surface hardening effect induced by SMA process. Improved tribological properties have been found for low-temperature plasma carburizing (LTPC) treated AISI 304 during pin-on-disc wear test [14]. Previously, 2D parameters such as root mean square roughness (R q ), skewness (R sk ), and kurtosis (R ku ) have been used for characterizing the worn surfaces.…”
Section: Introductionmentioning
confidence: 99%
“…Compared to 303 steel, abrasive wear is more dominant compared to adhesive wear mechanism which can be seen explicitly in Figure 2a. Grooves are formed due to scratches of debris and adhesive wear is overwhelmed [25][26][27]. A mild adhesive wear can be related with metal removal zones on the wear surface.…”
Section: Optical Microscope Investigationsmentioning
confidence: 99%
“…As a result of the study, it was found that the material of the needles is not made of 316L commercially marked austenitic stainless steel, but of a more general, not very biocompatible alloy, 1.4301 steel. The stress of stabbing the skin is abrasive, the wear properties of these steel types are not outstanding [11,12]. Poor wear resistance in medical devices is unfavourable, as particles detached during the wear process can cause irritation if they enter the body, especially the two main alloys of the steel type: chromium and nickel [13].…”
Section: In Vivo Damaged Needlesmentioning
confidence: 99%